Distress tolerance but not impulsivity predicts outcome in concurrent treatment for posttraumatic stress disorder and substance use disorder. Issue 4 (4th July 2018) - Levy, Hannah C.; Wanklyn, Sonya G.; Voluse, Andrew C.; Connolly, Kevin M.
ABSTRACT: Posttraumatic stress disorder (PTSD) and substance use disorder (SUD) commonly co-occur. Emerging research suggests that both distress tolerance and impulsivity may underlie this comorbidity. However, to our knowledge no studies have examined whether these 2 constructs predict outcome in PTSD-SUD treatment. The current study investigated whether pretreatment distress tolerance and impulsivity predicted posttreatment PTSD and cravings severity in a sample of 70 Veterans receiving concurrent treatment for PTSD and SUD in a residential day treatment program. Veterans completed measures of symptom severity before and after treatment. Results demonstrated that pretreatment distress tolerance predicted posttreatment PTSD severity while controlling for pretreatment PTSD. By contrast, pretreatment impulsivity was not predictive of posttreatment PTSD while controlling for pretreatment values. Neither distress tolerance nor impulsivity predicted posttreatment cravings severity. The findings support the notion that distress tolerance may help to explain the co-occurrence of PTSD and SUD and suggest that targeting this construct in PTSD-SUD treatment may be important for successful outcomes.